Chemical composition and biological activity of the essential oil of Ballota hispanica (L.) Benth. growing wild in Sicily. (2nd September 2016) - Riccobono, L.; Ben Jemia, M.; Senatore, F.; Bruno, M.
Abstract : Ballota L. comprises several relevant species largely used for their excellent therapeutic properties. Ballota hispanica (L.) Benth. is widely used in herbal medicine, and it is sold in herbalist shops for its sedative and antispasmodic properties. Considering its traditional medicinal use and the lack of scientific studies on the volatile components of this species as well as on its biological activities, in this study the chemical composition of the essential oil from aerial parts of B. hispanica, collected in Sicily, was evaluated by gas chromatography and gas chromatography–mass spectrometry. α-Elemol was the most abundant component of the oil (10.9%), followed by α-ylangene (8.5%), γ-dodecalactone (5.1%), and manoyl oxide (4.8%). A comparison was made of the composition of the different Ballota taxa studied so far showing a peculiar profile of B. hispanica . Futhermore, the antimicrobial and the free radical scavenging activities of the oil were determined.